Phylogenomic analysis of seal lice reveals codivergence with their hosts. (4th March 2019) - Leonardi, María Soledad; Virrueta Herrera, Stephany; Sweet, Andrew; Negrete, Javier; Johnson, Kevin P.
Abstract: Lice are considered a model system for studying the process of cospeciation because they are obligate and permanent parasites and are often highly host‐specific. Among lice, species in the family Echinophthiriidae Enderlein (Anoplura) are unique in that they infest mammalian hosts with an amphibious lifestyle, i.e. pinnipeds and the river otter. There is evidence that the ancestor of this group infested the terrestrial ancestor of pinnipeds, which suggests these parasites coevolved with their hosts during the transition to marine environments. However, there has been no previous study investigating the phylogenetic relationships among sucking lice parasitizing seals and sea lions. To uncover the evolutionary history of these parasites, we obtained genomic data for Antarctophthirus microchir Trouessart and Neumann (from two hosts), Antarctophthirus carlinii Leonardi et al., Antarctophthirus lobodontis Enderlein, Antarctophthirus ogmorhini Enderlein, Lepidophthirus macrorhini Enderlein, and Proechinophthirus fluctus Ferris. From genomic sequence reads, we assembled > 1000 nuclear genes and used these data to infer a phylogenetic tree for these lice. We also used the assembled genes in combination with read‐mapping to estimate heterozygosity and effective population size from individual lice. Our analysis supports the monophyly of lice from pinnipeds and uncovers phylogenetic relationships within the group. Surprisingly, we found that A. carlinii, A. lobodontis, and A. ogmorhini have very little genetic divergence among them, whereas the divergence between different geographic representatives of A. microchir indicate that they are possibly different species. Nevertheless, our phylogeny of Echinophthiriidae suggests that these lice have consistently codiverged with their hosts with minimal host switching. Population genomic metrics indicate that louse effective population size is linked to host demographics, which further highlights the close association between pinnipeds and their lice. Abstract : We investigated the phylogenetic relationships among sucking lice (Anoplura: Echinophthiriidae) parasitizing seals and sea lions. Our results suggest that echinophthiriids codiverged with their hosts with minimal host switching. Population genomic metrics indicate that louse effective population size is linked to host demographics.